PENGARUH HARGA, BRAND AMBASSADOR, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK SCARLETT WHITENING INDONESIA DI TOKOPEDIA - Oktavia, Erica Bella; Fatimah, Feti; Puspitadewi, Ira (Growth, 2022)
The business world continues to experience very significant developments in the current era. This trend continues to move from one generation to another following the times. In this modern era, beauty manufacturers pamper their consumers by offering a variety of beauty products and all their advantages. This study aims to analyze and examine the role of price, brand ambassador, brand image, and product quality on purchasing decisions on Indonesian Scarlett Whitening products at Tokopedia. The type of data in this study used quantitative data in the form of an online questionnaire. The sample population used in this study was 110 respondents with a non-probability sampling technique. Data collection techniques include primary data and secondary data. The data collection technique used a Likert scale. The analytical tool in this study uses multiple linear regression analysis which is supported by instrument testing, classical assumption test, and hypothesis testing. The results of this study prove that price has a significant effect on purchasing decisions with a significance level of 0.001 which is smaller than 0.05 with a coefficient of 3.307. Brand Ambassador has a significant effect on purchasing decisions with a significance level of 0.000 which is smaller than 0.05 with a coefficient of 7.040. Brand Image has a significant effect on purchasing decisions with a significance level of 0.000 less than 0.05 with a coefficient of 4.005 and product quality has a significant effect on purchasing decisions with a significance level of 0.028 which is smaller than 0.05 with a coefficient of 3.297.